INVESTIGATION OF THE PROPERTIES OF LITHIUM-CONTAINING CERAMICS BASED ON LOW-PLASTIC CLAY - Filippova, Lubov; Akimova, Anastasiya; Pikalov, Evgeniy; Selivanov, Oleg (IIUM Engineering Journal, 2024)
Nowadays the production of construction materials and items is a multi-tonnage and actively developing production sphere. The regulatory requirements imposed on construction materials and products provide the assessment of their quality and application efficiency in construction or reconstruction of buildings and structures. The constantly increasing regulatory requirements and the limited availability of high-quality natural reserves demand the rapid development of new raw material resources. This paper presents the results of charge composition development based on low-plasticity clay, which has seen limited application due to the poor performance of items produced from it. However, certain functional additives can be introduced for producing high-quality materials. In this work, alongside lithium carbonate, the following additives have been considered: boric acid used as flux and titanium dioxide as a vitreous phase source. The lithium carbonate effect on total and open porosity, density, thermal conductivity, water absorption, frost resistance, compressive and bending strength has been studied. On the one hand lithium carbonate was found to demonstrate a pore-forming effect due to its decomposition during firing. On the other hand, lithium oxide formed during the additive decomposition facilitated the viscosity reduction of the vitreous phase during firing and its strength increase after cooling. Lithium oxide, similar to boric acid, is a flux, which makes further temperature reduction of liquid-phase sintering possible while preserving the surface self-glazing effect and the formation of the closed-pored internal structure of ceramics. The lithium carbonate pore-forming effect prevails over the flux-hardening and therefore, the amount this additive should be limited to obtain high performance properties and the compliance of resulting ceramics with regulatory requirements. The resulting ceramic material can be used for manufacturing products for buildings’ and structures’ plinth lining. ABSTRAK: Pada masa kini, pengeluaran bahan dan barangan pembinaan adalah dalam gandaan tan dan aktif dibangunkan terutama dalam bidang pengeluaran. Keperluan pengawalseliaan bahan dan produk pembinaan menyediakan aplikasi penilaian kualiti dan kecekapan pembinaan atau pembinaan semula bangunan dan struktur. Peningkatan berterusan terhadap keperluan pengawalseliaan dan ketersediaan rizab semula jadi berkualiti tinggi yang terhad menuntut kepada pembangunan pesat sumber bahan mentah baru berkembang. Kajian ini memperkenalkan hasil pembangunan komposisi caj berdasarkan tanah liat keplastikan rendah, di mana aplikasi terhad kepada keburukan bahan yang dihasilkan, namun bahan tambahan tertentu boleh diperkenalkan bagi menghasilkan bahan berkualiti tinggi. Menggunakan litium karbonat bersama bahan tambahan berikut: asid borik digunakan sebagai fluks dan titanium dioksida sebagai sumber fasa vitreus, telah diambil kira dalam kajian ini. Kesan litium karbonat pada keliangan, ketumpatan, kekonduksian terma, penyerapan air, rintangan fros, kekuatan mampatan dan lenturan telah dikaji. Litium karbonat didapati menunjukkan kesan pembentukan liang dalam proses penguraian semasa pembakaran. Sebaliknya, litium oksida dibentuk semasa penguraian aditif dan membantu dalam pengurangan kelikatan fasa vitreus semasa pembakaran dan kekuatannya meningkat selepas penyejukan. Litium oksida, serupa dengan asid borik, adalah fluks, berpotensi menyebabkan suhu sinteran terus berkurang pada fasa cecair sambil mengekalkan kesan kilauan pada permukaan kaca dan menutup pembentukan struktur liang dalaman seramik. Kesan pembentukan liang litium karbonat adalah mengatasi pengerasan fluks. Oleh itu, jumlah bahan tambah ini harus dihadkan bagi mencapai piawaian dan prestasi tinggi seramik yang terhasil. Bahan seramik yang terhasil ini boleh digunakan sebagai lapisan plint bangunan dan struktur dalam pembuatan produk.